وضع اللغة العربية في باكستان: الواقع والمأمول والخطر الخفي المتسرب بثوب تدريس القرآن الكريم بدون اللغة العربية: The Position of Arabic Language in Pakistan: Facts, Hopes and the Dangerous Notion of Teaching Quran without Learning Arabic - Dr. Shair Ali Khan,; Dr. Arif Siddiq, (Al Manhal Research Journal, 2025)
Arabic language is the oldest and the most sacred language being the selected language of Allah for His last revelation. Arabic has a unique linguistic system which no other language has. It is the richest language in terms of vocabulary, roots, meters, and moods. It is the mother tongue of the last Prophet Muhammad (peace be upon him) who was long awaited by the Jews. When they confirmed his arrival in the Ismaelites, they turned into his severe enemies. They tried not only to harm his personality, his message but even tried to degrade the language he spoke, in which he revealed the last message of Allah.Various studies showed strong movements against Arabic language starting from Peter the Venerable who started the polemic Project of distorting the Islamic religious texts. Under this project Robbert of Kitton translated the Quran directly from Arabic into Latin in 1143 AD. This translation deadly influenced the west. Then Glade Stone; the Prime Minister of the Great Britian who initiated the movement to stop people from Quran through stopping them from learning the language of this Book. The Arabic in Pakistan is well popular and the loved one due to being the language of the Quran and mother tongue of the Last Prophet Muhammad (peace be upon him). It is taught in the schools, colleges and universities along with being mediam of instruction in the religious schools (Madrasa). In the recent years, suddenly there apeared voices that focus on teaching the Holy Quran without learning Arabic or its grammar. They have devised their specific methods through which they are teaching the Quran. The article tries to find out the danger of such methods whereas there is a long history of efforts and struggles for induting Arabic in the Education system of Pakistan. By such notions they create a big hinderence for those who learn Arabic for understanding the Holy Book; the Quran.